Popolo, popolare, populismo - Dei, Fabio (International Gramsci Journal, 2023)
The influence of Gramsci in post-war Italian anthropology has mainly concerned the redefinition of the sphere of popular culture in terms of the hegemony-subalternity relationship. The 1950s “folklore debate”, as it was termed, revolving around the ideas of Gramsci and De Martino, completely redefined the tradition of positivistic folklore studies. In the 1960s, then, a new discipline for the study of popular culture was founded on explicit Gramscian bases – “demology”. In this paper, I examine these moments of the scientific debate in the light of the problem of political and cultural “populism”: in other words, the problem of a certain degree of autonomy in the cultural productions of subaltern classes. I argue that demology, from its very beginnings, confused the autonomy of the subaltern with the autonomy of the academic discipline. Trying to isolate “real” folklore products from hegemonic ones and from mass culture, demologists lost sight of the historical dimension prevailing in both Gramsci and De Martino. In a sense, the current crisis of demology has mainly to do with the inability to deal with the problem of populism and its changing historical faces.